2019
DOI: 10.1186/s12872-019-1224-y
|View full text |Cite
|
Sign up to set email alerts
|

Creating and disseminating a home-based cardiac rehabilitation program: experience from the Veterans Health Administration

Abstract: Background: Cardiac rehabilitation (CR) programs provide significant benefit for people with cardiovascular disease. Despite these benefits, such services are not universally available. We designed and evaluated a national home-based CR (HBCR) program in the Veterans Health Administration (VHA). The primary aim of the study was to examine barriers and facilitators associated with site-level implementation of HBCR. Methods: This study used a convergent parallel mixed-methods design with qualitative data to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Previous work has reported that factors such as leadership support, funding, and institutional contribute to CR delivery. 24,25 This study adds further qualitative data to support these facilitators, and adds information on organizational factors that contribute to technology adoption for CR programs, including equipment and work ow modi cations for CR staff.…”
Section: It Was Very Cost Effective For Him Because He Was Catching Cmentioning
confidence: 91%
“…Previous work has reported that factors such as leadership support, funding, and institutional contribute to CR delivery. 24,25 This study adds further qualitative data to support these facilitators, and adds information on organizational factors that contribute to technology adoption for CR programs, including equipment and work ow modi cations for CR staff.…”
Section: It Was Very Cost Effective For Him Because He Was Catching Cmentioning
confidence: 91%
“…The study protocol was approved by the Internal Review Board at PVAMC. The HBCR program at PVAMC is supported by the VA Office of Rural Health HBCR Program, 14 with the goal of expanding CR access to Veterans with eligible CR diagnoses. Medical records were reviewed from consecutive patients enrolled in the HBCR program at PVAMC, Rhode Island, from November 2017 to March 2020.…”
Section: Methodsmentioning
confidence: 99%
“…To accomplish this, a variety of commercial and clinician-centric models have been deployed for use in both the synchronous and asynchronous settings. 10,12,24,26,44,49 Educational presentations can be incorporated during synchronous virtual sessions and allow the opportunity for patient participation. Screen sharing of PowerPoint (Microsoft) presentations or short videos to supplement the discussion can add interest and value.…”
Section: Patient Educationmentioning
confidence: 99%